1995
DOI: 10.1148/radiology.196.1.7784567
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid flow waveforms: analysis in patients with Chiari I malformation by means of gated phase-contrast MR imaging velocity measurements.

Abstract: CSF flow waveform analysis helps demonstrate abnormalities in CSF flow at the foramen magnum and the benefits of decompressive surgery in patients with the Chiari I malformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
84
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(94 citation statements)
references
References 0 publications
7
84
0
3
Order By: Relevance
“…It is generally agreed that many of the symptoms and signs associated with Chiari I malformation are attributed to abnormal CSF circulation between the head and the spine secondary to obstruction of the foramen magnum. 3,6,[9][10][11]13,25,26 Williams and others 1,4-6 have previously demonstrated this in patients with Chiari I malformation. On the basis of these results, we hypothesize that in patients with Chiari I malformation with a significant foramen magnum obstruction, the immediate postValsalva rebound in CSF flow shown here will be either absent or significantly reduced.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…It is generally agreed that many of the symptoms and signs associated with Chiari I malformation are attributed to abnormal CSF circulation between the head and the spine secondary to obstruction of the foramen magnum. 3,6,[9][10][11]13,25,26 Williams and others 1,4-6 have previously demonstrated this in patients with Chiari I malformation. On the basis of these results, we hypothesize that in patients with Chiari I malformation with a significant foramen magnum obstruction, the immediate postValsalva rebound in CSF flow shown here will be either absent or significantly reduced.…”
Section: Discussionmentioning
confidence: 82%
“…As a result, most cine-PC studies of CSF flow have only been used during quiet breathing, both in healthy participants and in patients with suspected CSF circulation abnormalities. [7][8][9][10][11][12][13][14] The 1 exception is a 2006 abstract by Wentland et al 15 reporting CSF flow during rest and Valsalva by using an undersampled projection reconstruction method with data acquisi-tion times of as little as 16 heartbeats. For healthy participants, however, only minimal differences in flow were seen.…”
mentioning
confidence: 99%
“…These studies have visualized and partially quantified cyclical CSF flow in patients with Chiari I malformation. [1][2][3][4][5][6][7][8][9][10][11][12][13] Investigators using axial-imaging-plane PCMR have measured CSF velocities in the subarachnoid space at the foramen magnum. Other investigators, using sagittal PCMR, have demonstrated CSF oscillatory flow in the midline over multiple cervical spinal levels, with limited accuracy, because of introvoxel dephasing.…”
mentioning
confidence: 99%
“…7,8 When flow images are acquired in a sagittal plane, flow patterns over multiple spinal levels are shown but usually only in the midline, where the velocities tend not to achieve their greatest magnitude. 9,10 Furthermore, typical axial CSF flow measurements with PCMR only capture the velocity vector perpendicularly because of the reduction in scanning time and the difficulty in accurately measuring the very slow velocity components in the anteroposterior and left-right direction. Additionally, PCMR does not directly measure CSF pressures, which are thought to be more relevant than the actual velocities in understanding of the pathogenesis of syrinx formation in patients with Chiari I malformation.…”
mentioning
confidence: 99%